Water potential control of turgor‐driven tracheid enlargement in Scots pine at its xeric distribution edge. Issue 1 (26th September 2019) - Cabon, Antoine; Fernández‐de‐Uña, Laura; Gea‐Izquierdo, Guillermo; Meinzer, Frederick C.; Woodruff, David R.; Martínez‐Vilalta, Jordi; De Cáceres, Miquel
Summary: The extent to which water availability can be used to predict the enlargement and final dimensions of xylem conduits remains an open issue. We reconstructed the time course of tracheid enlargement in Pinus sylvestris trees in central Spain by repeated measurements of tracheid diameter on microcores sampled weekly during a 2 yr period. We analyzed the role of water availability in these dynamics empirically through time‐series correlation analysis and mechanistically by building a model that simulates daily tracheid enlargement rate and duration based on Lockhart's equation and water potential as the sole input. Tracheid enlargement followed a sigmoid‐like time course, which varied intra‐ and interannually. Our empirical analysis showed that final tracheid diameter was strongly related to water availability during tracheid enlargement. The mechanistic model was calibrated and successfully validated ( R 2 = 0.92) against the observed tracheid enlargement time course. The model was also able to reproduce the seasonal variations of tracheid enlargement rate, duration and final diameter ( R 2 = 0.84–0.99). Our results support the hypothesis that tracheid enlargement and final dimensions can be modeled based on the direct effect of water potential on turgor‐driven cell expansion. We argue that such a mechanism is consistent with other reported patterns of tracheid dimension variation.